WOMEN'S CONTESTATION IN THE ELECTORAL MAP IN BANTEN PROVINCE IN THE FRAME OF ISLAMIC LAW AND GENDER POLITICS - PITROTUSSAADAH, PITROTUSSAADAH; Zakaria Syafe’i; Nina Chairina; Sultan Isnansyah Fazri (AL-QISTHAS: JURNAL HUKUM DAN POLITIK, 2024)
The goal of this research is to determine the contestation of women in the Political Islamic law and gender in Banten Province, as well as a review of Islamic law political on women's contestation in election political maps. This study employs a qualitative method of content analysis. Women presently lead 37.5 percent of districts/cities in Banten Province. Additionally, in the previous government position, the figure reached 50%. Similarly, two elections were won by women at the provincial level in the four gubernatorial elections that were held. The substantial participation of women in Banten's election campaign is fascinating to investigate. The findings of this study reveal that the engagement of women in the political map of the regional election in Banten was due to the freedom, opportunity, and chance for women to participate in the political sphere. Furthermore, the involvement and participation of the family were significant owing to their typical family background as politicians who previously served in the same position, which is known as the relay and inheritance of family leadership. Some refer to it as a familial political dynasty. According to an examination of Islamic law, women's participation in the political map of the regional elections in Banten does not contravene the siyasa syar'iyyah because it is included in the siyasa dusturiyyah. Furthermore, Islam does not forbid women from participating in politics.